2010
DOI: 10.1117/12.863372
|View full text |Cite
|
Sign up to set email alerts
|

Chiral biomarkers and microfossils in carbonaceous meteorites

Abstract: Homochirality of the biomolecules (D-sugars of DNA and RNA and L-amino acids of proteins) is a fundamental property of all life on Earth. Abiotic mechanisms yield racemic mixtures (D/L=1) of chiral molecules and after the death of an organism, the enantiopure chiral biomolecules slowly racemize. Several independent investigators have now established that the amino acids present in CI1 and CM2 carbonaceous meteorites have a moderate to strong excess of the L-enantiomer. Stable isotope data have established that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…7 During the past 14 years, many large, complex filaments, consortia and mat assemblages have been found with undeniable biological characteristics that were interpreted as indigenous microfossils in carbonaceous meteorites during both independent and collaborative SEM, ESEM and FESEM investigations carried out in the United States and Russia. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Many of the filamentous and coccoidal microstructures found during this research were consistent with forms found half a century ago by earlier researchers (e.g., Nagy, Claus, Fitch, Palik, Timofeyev and van Landingham) and interpreted as indigenous microfossils of blue-green algae (cyanophytes), bacteria, and acritarchs or dismissed as recent bacterial contaminants or pollen grains. [23][24][25][26][27][28][29][30][31][32] The filaments detected at NASA/MSFC were imaged with secondary and backscattered electron detectors and analyzed by EDS to obtain spot data and 2D x-ray maps at voltages ranging from 5 keV to 15 keV.…”
Section: Introductionsupporting
confidence: 75%
“…7 During the past 14 years, many large, complex filaments, consortia and mat assemblages have been found with undeniable biological characteristics that were interpreted as indigenous microfossils in carbonaceous meteorites during both independent and collaborative SEM, ESEM and FESEM investigations carried out in the United States and Russia. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Many of the filamentous and coccoidal microstructures found during this research were consistent with forms found half a century ago by earlier researchers (e.g., Nagy, Claus, Fitch, Palik, Timofeyev and van Landingham) and interpreted as indigenous microfossils of blue-green algae (cyanophytes), bacteria, and acritarchs or dismissed as recent bacterial contaminants or pollen grains. [23][24][25][26][27][28][29][30][31][32] The filaments detected at NASA/MSFC were imaged with secondary and backscattered electron detectors and analyzed by EDS to obtain spot data and 2D x-ray maps at voltages ranging from 5 keV to 15 keV.…”
Section: Introductionsupporting
confidence: 75%
“…Therefore the detection of racemic mixtures of amino acids or other biologically produced molecules could simply indicate they are ancient rather than produced by abiotic mechanisms. Several of the chiral biomolecules found in Orgueil, Murchison and other carbonaceous meteorites exhibit an excess of the L-enantiomer that is much greater that can be produced by any known abiotic production/amplification mechanism, but consistent with ancient life processes [26].…”
Section: Introductionmentioning
confidence: 64%
“…Therefore the detection of racemic mixtures of amino acids or other biologically produced molecules could simply indicate they are ancient rather than produced by abiotic mechanisms. Several of the chiral biomolecules found in Orgueil, Murchison and other carbonaceous meteorites exhibit an excess of the L-enantiomer that is much greater that can be produced by any known abiotic production/amplification mechanism, but consistent with ancient life processes [26].…”
Section: Introductionmentioning
confidence: 64%